The course of sexual interest and enjoyment in head and neck cancer patients treated with primary (chemo)radiotherapy. (August 2018) - Melissant, H.C.; Jansen, F.; Schutte, L.E.R.; Lissenberg-Witte, B.I.; Buter, J.; Leemans, C.R.; Sprangers, M.A.; Vergeer, M.R.; Laan, E.T.M.; Verdonck-de Leeuw, I.M.
Highlights: Less sexual interest and enjoyment is often reported in HNC patients. Less sexuality is most prevalent 6 weeks after treatment (60%). Social contact, older age, weight loss and constipation are associated factors. Female gender and social functioning are associated factors at 6-month follow-up. Abstract: Introduction: The aim of this prospective study was to investigate the course of sexual interest and enjoyment in relation to sociodemographic and clinical factors, health-related quality of life (HRQOL), and symptoms of psychological distress in head and neck cancer (HNC) patients treated with primary (chemo)radiotherapy. Methods: HNC patients (n = 354) completed patient-reported outcome measures (PROMs) on HRQOL (EORTC QLQ-C30 and QLQ-H&N35, including the sexuality subscale covering less sexual interest and enjoyment), and psychological distress (HADS) pretreatment, at 6-week follow-up and at 3-, 6-, 12-, 18-, and 24-month follow-up (i.e., after treatment). Linear mixed models were used to analyze the course of sexuality from pretreatment to 24-month follow-up, and to investigate its relation to sociodemographic and clinical factors, HRQOL, and psychological distress as measured at baseline, and to investigate the course of sexuality from 6- to 24-month follow-up in relation to these factors measured at 6-month follow-up. Results: Before start of treatment, 37% of patients reported having less sexuality, which increased to 60% at 6-week follow-up, and returned to baseline level from 12-month follow-up onwards. Older age ( p  = 0.037) and trouble with social contact ( p <  0.001), weight loss ( p  = 0.013), and constipation ( p  = 0.041) before treatment were associated with less sexuality over time. Female gender ( p  = 0.021) and poor social functioning ( p  < 0.001) at 6-month follow-up were associated with less sexuality from 6- to 24-month follow-up. Discussion: Less sexuality is often reported in HNC patients treated with (chemo)radiotherapy. Using PROMs in clinical practice may help identify patients who might benefit from supportive care targeting sexuality.